George Washington's secret six [compact disc, unabridged] : the spy ring that saved the American Revolution - Kilmeade, Brian; Yaeger, Don (Penguin Audio, 2013)
Shares the true story of an anonymous group of spies who played important roles in winning the Revolutionary War, documenting how they risked their lives to obtain crucial intelligence for General Washington using sophisticated tactics and complex codes.